The sawtooth EKG pattern of typical atrial flutter is not related to slow conduction velocity at the cavotricuspid isthmus. (14th September 2017) - Sau, Arunashis; Sikkel, Markus B.; Luther, Vishal; Wright, Ian; Guerrero, Fernando; Koa‐Wing, Michael; Lefroy, David; Linton, Nicholas; Qureshi, Norman; Whinnett, Zachary; Lim, Phang Boon; Kanagaratnam, Prapa; et al.
Abstract: Introduction: We hypothesized that very high‐density mapping of typical atrial flutter (AFL) would facilitate a more complete understanding of its circuit. Such very high‐density mapping was performed with the Rhythmia TM (Boston Scientific) mapping system using its 64 electrode basket catheter. Methods and results: Data were acquired from 13 patients in AFL. Functional anatomy of the right atrium (RA) was readily identified during mapping including the Crista Terminalis and Eustachian ridge. The leading edge of the activation wavefront was identified without interruption and its conduction velocity (CV) was calculated. CV was not different at the cavotricuspid isthmus (CTI) compared to the remainder of the RA (1.02 vs. 1.03 m/s, P = 0.93). The sawtooth pattern of the surface electrocardiogram (EKG) flutter waves was compared to the position of the dominant wavefront. The downslope of the surface EKG flutter waves represented on average 73% ± 9% of the total flutter cycle length. During the downslope, the activation wavefront traveled significantly further than during the upslope (182 ± 21 milliseconds vs. 68 ± 29 milliseconds, P < 0.0001) with no change in CV between the two phases (0.88 vs. 0.91 m/s, P = 0.79). Conclusion: CV at the CTI is not slower than other RA regions during typical AFL. The gradual downslope of the sawtooth EKG is not due to slow conduction at the CTI suggesting that success of ablation at this site relates to anatomical properties rather than the presence of a "slow isthmus."